ANALYSIS OF THE ROLE OF THE BPKB ARRUM WITH RAHN AGREEMENT ON UMKM IN TANJUNG BUMI BANGKALAN - Putri, Avia Agustina; Dony Burhan Noor Hasan (I-Finance Journal, 2024)
This study aims to explore the role of Arrum Financing Products through the Telaga Biru Sharia Pawnshop Branch in providing inclusive financial access for Micro, Small, and Medium Enterprises (MSMEs). The informants in this study include 10 MSME actors who use Arrum Financing products as well as employees or management of the Telaga Biru Sharia Pawnshop Branch. Using a qualitative approach with the help of Nvivo software for data analysis. Arrum BPKB financing with the Rahn contract has a positive impact on the growth and sustainability of MSMEs in Tanjung Bumi from the perspective of sharia principles, and is an innovative and effective solution that supports MSMEs by facilitating financial access, reducing risks, and encouraging local economic development. The importance of sharia financing products in financial inclusion and suggested that Sharia Pawnshops continue to develop and promote Arrum Financing for wider benefits for MSMEs. The conclusion shows that Arrum BPKB financing with a rahn contract is in accordance with sharia principles and plays a very important role in supporting MSMEs in Tanjung Bumi, Bangkalan, by making a significant contribution through satisfactory services, efficient processes, and financing flexibility.